An isoform of the rod photoreceptor cyclic nucleotide-gated channel β subunit expressed in olfactory neurons - Sautter, Andrea (The National Academy of Sciences, 1998)
Sensory transduction in olfactory neurons involves the activation of a cyclic nucleotide-gated (CNG) channel by cAMP. Previous studies identified a CNG channel α subunit (CNG2) and a β subunit (CNG5), which when heterologously expressed form a channel with properties similar but not identical to those of native olfactory neurons. We have cloned a new type of CNG channel β subunit (CNG4.3) from rat olfactory epithelium. CNG4.3 derives from the same gene as the rod photoreceptor β subunit (CNG4.1) but lacks the long, glutamic acid-rich domain found in the N terminus of CNG4.1. Northern blot and in situ hybridization revealed that CNG4.3 is expressed specifically in olfactory neurons. Expression of CNG4.3 in human embryonic kidney 293 cells did not lead to detectable currents. Coexpression of CNG4.3 with CNG2 induced a current with significantly increased sensitivity for cAMP whereas cGMP affinity was not altered. Additionally, CNG4.3 weakened the outward rectification of the current in the presence of extracellular Ca(2+), decreased the relative permeability for Ca(2+), and enhanced the sensitivity for l-cis diltiazem. Upon coexpression of CNG2, CNG4.3, and CNG5, a conductance with a cAMP sensitivity greater than that of either the CNG2/CNG4.3 or the CNG2/CNG5 channel and near that of native olfactory channel was observed. Our data suggest that CNG4.3 forms a subunit of the native olfactory CNG channel. The expression of various CNG4 isoforms in retina and olfactory epithelium indicates that the CNG4 subunit may be necessary for normal function of both photoreceptor and olfactory CNG channels.